(x+11)(x-1)(x-3) =
(x² - x + 11x - 11)(x-3) =
(x² + 10x - 11)(x-3) =
x³ - 3x² + 10x² - 30x - 11x + 33 =
x³ + 7x² - 41x + 33
2007-06-08 13:44:14
·
answer #1
·
answered by MathGuy 6
·
0⤊
0⤋
I assume you mean: (x+11)(x-1)(x-3)
= [(x+11)(x-1)] (x-3)
= (x² - x + 11x - 11) (x-3)
= (x³ + 10x -11) (x-3)
= x³ - 3x² + 10x² - 30x - 11x + 33
= x³ + 7x² - 41x + 33
2007-06-08 20:52:33
·
answer #2
·
answered by jurassicko 4
·
0⤊
0⤋
product is (x+11) (x-1) (x-3)
if you simplify this to a polynomial it is not a product anymore
don't even place an equality = because it becomes an equation
2007-06-08 22:52:50
·
answer #3
·
answered by CPUcate 6
·
0⤊
0⤋
(x-1)*(x-3)==x^2-4x+3
then multiply this equation by x
then multiply by 11 and add like terms
(x^2-4x+3)*x= x^3-4x^2+3x
(x^2-4x+3)*11= 11x^2-44x +33
now add
x^3+7x^2-41x+33
2007-06-08 20:49:54
·
answer #4
·
answered by jon d 3
·
0⤊
0⤋
x^3+7x^2-41x+33
2007-06-08 20:46:34
·
answer #5
·
answered by lynchy_hi 2
·
0⤊
0⤋
equale +2 or factor of tow postive it asking for postive or part 2 for scand answer would be adding negathives x-13 to total it , or part 3 could be zero there difffent answers parts to each porblum just get you have used diffent combonations math fuigers....
2007-06-08 20:46:56
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋
(x+11)(x-1)=x^2+10x-11(x-3)=
x^3-3x^2+10x^2-30x-11x+33
x^3+7x^2-41x+33
2007-06-08 21:13:49
·
answer #7
·
answered by Dave aka Spider Monkey 7
·
0⤊
0⤋
(x-1)(x-3)=x²-4x+3
(x+11)(x²-4x+3)=x³-4x²+3x+11x²-44x+33
(x+11)(x-1)(x-3)=x³+7x²-41x+33
2007-06-08 20:45:16
·
answer #8
·
answered by yupchagee 7
·
0⤊
0⤋